Microsoft windows 7 : introductory - Johnson, Steve; Johnson, Steve (Australia : Course Technology Cengage Learning, 2010)
This book is an ideal learning tool for a wide range of learners -- the "rookies" will find the clean design easy to folow and focused with only essential information presented, and the "hotshots" will appreciate being able to move quickly through the lessons to find information they need without reading a lot of text. The design also makes this a great reference after the course is over!
Unit A: Introducing windows 7 -- Unit B: Working with windows programs -- Unit C: Managing files and folders -- Unit D: Customizing file and folder management -- Unit E: Customizing windows using the control panel -- Unit F: Securing your computer -- Unit G: Exploring the internet with Microsoft internet explorer -- Unit H: Exchanging mail and news
Includes index.
Keywords: MICROSOFT WINDOWS (COMPUTER FILE)